Exploring Youths’ Experiences of Attending a Rural Outreach School in Alberta - Ormandy, Matt; Ferdinands, Alexa; Mayan, Maria (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2025)
Outreach schools have existed for decades as an alternative for students who have struggled in mainstream education. Students at outreach schools have been cast as “failures” or “dropouts” due to their lack of success in mainstream schooling. Drawing on critical theoretical traditions in qualitative research, this article challenges these hegemonic discourses. This study uses semi-structured interviews with 25 young people (aged 14–19 years) who attended an outreach school in a rural community in Alberta. We identify three themes of participants’ experiences attending the outreach school: (1) discovering the outreach school, (2) changing views about education, and (3) planning for the future. The article concludes with a critical discussion of the discourses of choice and success regarding attendance at outreach schools. We draw attention to social structural forces that impact students at outreach schools in rural communities and constrain their education opportunities.